2023
DOI: 10.1007/s00170-023-11122-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on tool wear mechanism under cryogenic CO2-assisted minimum quantity lubrication technology

Abstract: Cryogenic CO 2 -assisted minimum quantity lubrication milling technology is a green processing technology with broad application prospects. Aiming at the problem of tool wear in the application of cryogenic CO 2 cooling assisted minimum quantity lubrication in di cult-to-machine materials and the in uence of relevant parameters on tool wear, this study used coated cemented carbide tools to perform milling experiments under cryogenic CO 2 -assisted minimum quantity lubrication technology conditions. The micromo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…On the one hand, the purpose of lubrication, cooling, and chip removal is achieved, which can prolong the tool life and improve the machining quality; on the other hand, it causes great damage to the natural environment, poses a threat to the health of machine tool operators [1][2][3] and results in high cost and consumption [4][5][6]. In recent years, minimum quantity lubrication (MQL) cutting technology has achieved good machining results [7,8]. Çamlı, et al [9] focused on the influence of MQL in the machining of steel parts for rail wheels, results showed that the MQL can reduce the surface roughness and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the purpose of lubrication, cooling, and chip removal is achieved, which can prolong the tool life and improve the machining quality; on the other hand, it causes great damage to the natural environment, poses a threat to the health of machine tool operators [1][2][3] and results in high cost and consumption [4][5][6]. In recent years, minimum quantity lubrication (MQL) cutting technology has achieved good machining results [7,8]. Çamlı, et al [9] focused on the influence of MQL in the machining of steel parts for rail wheels, results showed that the MQL can reduce the surface roughness and tool wear.…”
Section: Introductionmentioning
confidence: 99%